Audiovisualidades nos quadrinhos digitais: como se dá o tensionamento das molduras quadrinhos, audiovisual e software/interface nas AppHQs - Almeida, Émerson Vasconcelos (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation aims to make notes to answer the research problem that constitutes essentially the following question: "How audiovisual strategies, in combination with the dimensions of the software and the cultural interface operate on other frames of AppHQs?". For that, I operate on macroframes software/interface, comics and audiovisual, trying to understand how is the tension between them in empirical objects analyzed. The AppHQs are comics that have characteristics of digital applications and, therefore, follow a logic of software. The constitution of the methodology of this research relies on procedures originally proposed by Benjamin, Bergson and Kilpp. Besides these authors, others, like Dubois, Manovich and McLuhan are fundamental to understanding the audiovisual strategies present in AppHQs. The concept of comics presented throughout this dissertation is based on what Eisner and McClloud say about sequential art. This research advances regarding to the mapping audiovisual strategies used in AppHQs. Moreover, it also advancing methodologies for studies of this object.
Keywords: AppHQ; Audiovisual; Interface; Quadrinhos; Software; Estratégias; Strategies; Comics; ACCNPQ::Ciências Sociais Aplicadas::Comunicação